PENAFSIRAN HAKIM TENTANG KEBERADAAN STRUKTURAL LEMBAGA KEPOLISIAN SEBAGAI PENYELENGGARA NEGARA DAN PENEGAK HUKUM (KAJIAN TERHADAP PUTUSAN PENGADILAN NEGERI JAKARTA SELATAN NOMOR 04/PID.PRAP/2015) - R. Yosia Simamora (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The Corruption Eradication Commission (KPK) announced BudiGunawan as a suspect of corruption when he was Deputy Head of CareerDevelopment of Human Resources. South Jakarta District Court panel ofjudges Sarpin Rizaldi favor Budi Gunawan and express stipulation assuspect unauthorized and not legally binding. In its decision, the judgestated that the determination Sarpin Rizaldi Budi Gunawan suspects by theKPK is not legally valid. Judges considered that the Commission had noauthority to investigate cases that ensnare Budi Gunawan, because whenthe suspect is not included as an organizer of the state and law enforcer.With a variety of the above problems, the authors are keen to lift the titlethesis on "The interpretation of the judge about presence of police forcesAs organizers Structure Institute of State and Law Enforcement (StudyAgainst the South Jakarta District Court Decision No. 04 / Pid.prap /2015)".Based on the brief description of the background mentioned above,there are some things that are at issue in this research are: First, whetherthe interpretation Sarpin Rizaldi judge in examining and deciding the caseNo. 04 / Pid.prap / 2015 on the State management and law enforcement isright? Then secondly, what implications that arise after the verdict SarpinRizaldi in examining and deciding the case No. 04 / Pid.prap / 2015 onState administrators and law enforcement?The author define three theories become a rationale for this study,namely, the theory of legal interpretation, the theory of state officials andlaw enforcement, and the theory of legal certainty.Keywords: Interpretation of Laws - State Administrator - LawEnforcement